Statistical analysis of the influence of papillomavirus infection on human immune and antioxidative systems - Lapkauskaitė, Laura; Didžiapetrienė, Janina; Kazbarienė, Birutė (Lietuvos matematikos rinkinys, 2002)
There is not abstract.